IMPLEMENTASI PRINSIP TRANSPARANSI MELALUI PERATURAN PRESIDEN NO. 26 TAHUN 2010 PADA INDUSTRI EKSTRAKTIF - Dian Purnama Anugerah; Yuniarti Yuniarti (Universitas Airlangga, 2010)
Ekstraktive Industry is a major industry that support Indonesia’s national income. The monitoring system of ekstraktive industry should be based on good corporate governance and transparency principle. This is due to the regulation of mining law and the Investment Law in Indonesia. This Principle encourage Indonesia to be one of EITI members, through its participation in this organization, ekstraktive Industry in Indonesia were expected to maintain Indonesian welfare, as says in the constitution.